Calculation of the production of exhaust emissions in the laboratory conditions - Šarkan, Branislav; Hudec, Juraj; Sejkorová, Marie; Kuranc, Andrzej; Kiktová, Monika (Institute of Physics Publishing Ltd, 2021)
In the past, the type approval of road vehicles with regard to the production of pollutants was carried out exclusively in the form of laboratory tests. Laboratory tests determined the course of the vehicle’s driving cycle and the methodology for quantifying pollutants depending on the distance passed. The revision of EU legislation in 2016 brought changes in the field of type approval, in particular a change in the driving cycle and an additional driving test in the form of real drive emission. The paper discusses a matter of the possibility of using Commission Regulation (EU) 2017/1151 for the purpose of calculating emissions of road vehicles in their operation by applying the methodology of real drive emission. The research task was performed on a roller dynamometer on two vehicles in the simulation of the original New European Driving Cycle (NEDC) in laboratory conditions with the application of the methodology for calculating emissions from real drive emission. During the test, the method of calculating the exhaust flow by sensing the amount of fuel consumed and the amount of intake air was used. Significant data, such as mass air flow, air temperature, engine speed, vehicle speed was recorded via the electronic control unit. Recorded data obtained from emission tester, roller dynamometer and On Board Diagnostic (OBD) tool must be synchronised. Test results should be used in the field of comparison of the type approval emission level and the emission level in operation.
Výpočet produkce výfukových emisí v laboratorních podmínkách
Keywords: calculation; production; exhaust emissions; conditions; výfukové emise; produkce; laboratorní podmínky; výpočet